Arrears in Contributions to the Employment Social Security Administering Agency in the Perspective of State Financial Recovery - Puspadewi, Anak Agung Ayu Intan; Juniarta, Ida Bagus Gede Angga (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
BPJS is an entity that functions as the organizer of social security programs, structured as a public legal entity. Any policy issued by the Government is not always smooth or free from obstacles as desired by the Law. The current issue faced by BPJS is related to the outstanding BPJS contributions from employers or businesses. The purpose of this writing is to determine the position of the BPJS contribution arrears in relation to State Finance. The methodology used in this journal writing is Normative Methodology. Regarding State Finance, a fundamental aspect is the contribution from the State Budget (APBN) as stated in Law No. 17 of 2003 concerning State Finance. The connection with the arrears of BPJS Employment contributions is that when these contributions are not paid by employers or businesses, it leads to indirect losses to State Finance, because when BPJS Employment was established, the State had initial capital sourced from the APBN placed in BPJS Employment according to Law Number 24 of 2011 from the APBN. Therefore, in relation to the arrears of BPJS Employment contributions, the relevant authorities in the legal field can assist BPJS Employment in recovering State finances.